Flaky EU-1 molecular sieve as well as preparation method and application thereof
By selecting a specific SiO2 and Al2O3 ratio without adding seeds and using organic alkali, a thin sheet-like EU-1 molecular sieve was synthesized by one-step method, which solved the problem that the silicon-aluminum ratio of EU-1 molecular sieve is easily transformed when the silicon-aluminum ratio of EU-1 molecular sieve is high in the prior art, and the efficient and stable synthesis of EU-1 molecular sieve with high silicon-aluminum ratio is achieved, with better catalytic performance and hydrothermal stability.
Patent Information
- Application Number
- CN202311218030.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-20
AI Technical Summary
In the prior art, when the EU-1 molecular sieve is synthesized, the silicon-aluminum ratio is easily converted into ZSM-48 molecular sieve when the silicon-aluminum ratio is high, making it difficult to obtain a pure phase EU-1 molecular sieve, and the commonly used methods are complex and costly.
By selecting a specific SiO2 to Al2O3 ratio, a thin sheet-shaped EU-1 molecular sieve was synthesized by a one-step method without adding seeds and using organic bases, which had a high silicon-aluminum ratio and a high specific surface area.
It has achieved efficient and stable synthesis of EU-1 molecular sieve with high silicon-aluminum ratio, which has better catalytic performance and hydrothermal stability, and is suitable for industrial production.
Smart Images

Figure HDA0004459786290000011 
Figure HDA0004459786290000012 
Figure HDA0004459786290000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molecular sieves, and in particular to a flaky EU-1 molecular sieve and a preparation method and application thereof. Background Art
[0002] EU-1 molecular sieve was first synthesized by Casci in the 1980s using hexamethylammonium cation as a template. It has a one-dimensional ten-membered ring pore structure (0.58×0.41nm) and a twelve-membered ring side pocket (0.68×0.58nm). It belongs to the orthorhombic crystal system and the space group belongs to Cmma. EU-1 molecular sieve has a unique pore structure and exhibits good catalytic performance in reactions such as aromatic conversion, methanol to propylene (MTP) and naphtha cracking. For example, in the isomerization reaction of xylene, EU-1 molecular sieve exhibits excellent activity and selectivity, and is superior to mordenite (MOR) and ZSM-5 molecular sieves that have been industrially applied in terms of total C8 aromatic loss, disproportionation and alkyl transfer losses. Therefore, the synthesis of EU-1 molecular sieve is of great significance in both theoretical research and practical application.
[0003] In the prior art, hexamethylammonium bromide is often used as a template to synthesize EU-1 molecular sieve by hydrothermal method. This method can synthesize pure phase EU-1 molecular sieve when the silicon-aluminum ratio is lower than 120. However, when the silicon-aluminum ratio is higher, the surface activation energy of nucleation and crystallization of EU-1 molecular sieve are higher than those of ZSM-48 molecular sieve. The synthesized EU-1 molecular sieve is in a metastable state and is easily transformed into ZSM-48 molecular sieve, making it difficult to synthesize pure phase EU-1 molecular sieve.
[0004] To this end, people have improved the above method by introducing seed crystals or using organic bases, using composite templates and other means to obtain pure EU-1 molecular sieves or increase the silicon-to-aluminum ratio of EU-1 molecular sieves. For example: Xu et al. (Xu QH, Journal of Colloid and Interface Science, 2011, 358 (1): 252-260) effectively reduced the nucleation activation energy of high-silicon EU-1 molecular sieves by adding seed crystals to the system, thereby inhibiting the formation of ZSM-48 and preparing pure-phase high-silicon-to-aluminum ratio EU-1 molecular sieves. However, this method requires the preparation of seed crystals separately, and it is impossible to synthesize high-silicon EU-1 molecular sieves in one step, and the entire preparation process is relatively complicated. LI et al. (LI XF, Journal of Porous Materials, Journal of Porous Materials, 2016, 23 (6): 1557-1565) successfully improved the silicon-to-aluminum ratio of EU-1 molecular sieves using an organic base source tetraethylammonium hydroxide (TEAOH). They believe that TEAOH can effectively reduce the nucleation activation energy of high-silicon EU-1 molecular sieves. +It better matches the lower negative charge density in the high-silicon EU-1 molecular sieve framework, but this method uses the organic base TEAOH as the alkali source, which has a high cost. CN103301877A discloses a method for synthesizing high-silicon EU-1 in a microemulsion system formed by a water-insoluble organic solvent using hexamethylammonium and dibenzyldimethylammonium as a composite template, adding EU-1 seeds, and using inorganic salts and surfactants as co-promoters. This method requires the preparation of seeds or the use of a two-stage crystallization method, and the steps for preparing the EU-1 molecular sieve are relatively complicated. CN1259399A discloses a method for preparing EU-1 molecular sieve, which uses a template precursor to synthesize zeolite. During the synthesis, seeds can be added to shorten the crystallization time, but the synthesis time is long (more than 100h) and the yield is low (less than 5%). The prepared EU-1 molecular sieve has a relatively low silicon-aluminum ratio, with a maximum of 200.
[0005] In addition, the EU-1 molecular sieves in the prior art are usually rugby-shaped, and there are no reports of sheet-shaped EU-1 molecular sieves. Summary of the invention
[0006] In order to solve one of the above-mentioned technical problems existing in the prior art, the present invention provides a flaky EU-1 molecular sieve and a preparation method thereof. The EU-1 molecular sieve of the present invention is a flaky structure and has a high silicon-aluminum ratio. Compared with the EU-1 molecular sieve of the prior art with a non-flaky morphology (such as olive-shaped, rod-shaped, granular, etc.), it has a larger specific surface area and a higher hydrothermal stability, and has better catalytic performance. The preparation process of the present invention does not require the additional addition of crystal seeds and other additives, nor does it require the use of organic bases. A pure phase EU-1 molecular sieve with a high silicon-aluminum ratio can be prepared by a one-step method. The process is simple, the cost is low, the crystallization time is short, the product has a high degree of crystallinity, and the EU-1 molecular sieve with a high silicon-aluminum ratio can be efficiently and stably synthesized, which is suitable for industrial production.
[0007] In a first aspect, the present invention provides a sheet-like EU-1 molecular sieve, wherein the sheet thickness is 20-50 nm.
[0008] The EU-1 molecular sieve of the present invention is in the form of thin sheets, and has a morphology completely different from the existing EU-1 molecular sieve in the prior art. By improving the morphology and structure of the EU-1 molecular sieve, its performance in catalysis, adsorption, etc. can be further improved.
[0009] It should be noted that the sheet thickness described in the present invention is the average thickness of the sheet.
[0010] In some embodiments, the molecular sieve has a specific surface area greater than 200 m 2 ·g -1 .
[0011] In some embodiments, the molecular sieve has a silicon-aluminum molar ratio SiO2 / Al2O3 of 350-700. The EU-1 molecular sieve of the present invention has a high silicon-aluminum molar ratio. According to previous studies on molecular sieves, molecular sieves with a high silicon-aluminum ratio have weaker acidity and stronger thermal stability and hydrothermal stability. EU-1 molecular sieves with a high silicon-aluminum ratio have higher propylene selectivity when used in MTP reactions, which can significantly reduce C 5+ The production of hydrocarbons and maintain a high product P / E ratio.
[0012] In a second aspect, the present invention provides a method for preparing the flaky EU-1 molecular sieve described in the first aspect, comprising the following steps:
[0013] A mixed solution containing an inorganic alkali source, an aluminum source, a template, a silicon source and water is crystallized to obtain a flaky EU-1 molecular sieve; wherein, in the mixed solution, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the molar ratio of SiO2 to Al2O3 is 1:(0.001-0.003).
[0014] The method of the present invention uses a specific SiO2 and Al2O3 ratio to successfully synthesize a flake EU-1 molecular sieve without adding seed crystals, which is different from the morphology of the existing EU-1 molecular sieve (rugby ball shape, granular shape, etc.). In addition, the preparation method of the present invention does not use an organic base and has low cost.
[0015] In the present invention, there is no special requirement for the preparation method of the mixed solution. In some embodiments, the preparation method of the mixed solution comprises: adding an inorganic alkali source, an aluminum source, a template agent and a silicon source to water in sequence, stirring, and obtaining a gel mixed solution.
[0016] In the mixed solution of the present invention, the molar ratio of SiO2 to Al2O3 is 1:(0.001-0.003), for example, it can be 1:0.001, 1:0.0012, 1:0.0015, 1:0.0018, 1:0.002, 1:0.0022, 1:0.0025, 1:0.0028, 1:0.003 or any value therebetween, preferably 1:(0.0012-0.0025). The present invention can obtain flaky EU-1 molecular sieves with different silicon-aluminum molar ratios SiO2 / Al2O3 by adjusting the dosage ratio of the silicon source and the aluminum source in the mixed solution, and can control the silicon-aluminum molar ratio SiO2 / Al2O3 of the flaky EU-1 molecular sieve within the range of 350-700, thereby realizing a one-step method for rapidly and efficiently preparing a high silicon-aluminum molar ratio EU-1 molecular sieve.
[0017] In some embodiments, the inorganic base source is at least one of an alkali metal oxide, an alkali metal hydroxide, and an alkali metal carbonate. In some embodiments, the inorganic base source is an alkali metal hydroxide. In some embodiments, the inorganic base source is at least one of lithium hydroxide, sodium hydroxide, and potassium hydroxide.
[0018] In some embodiments, the silicon source is selected from one or more of silica sol, water glass and silicate.
[0019] In some embodiments, the aluminum source is selected from one or more of sodium aluminate, aluminum nitrate nonahydrate, pseudo-boehmite, and aluminum isopropoxide.
[0020] The template agent in the present invention can use a single template agent hexamethylammonium bromide to synthesize a flaky EU-1 molecular sieve with a high silicon-to-aluminum ratio. Other template agents such as benzyldimethylamine, tetramethylammonium bromide, tetraethylammonium bromide and tetrapropylammonium bromide can also be used in combination with hexamethylammonium bromide. The two can synergistically play the role of structure directing agent, template filler or balancing skeleton charge, thereby being able to synthesize a flaky EU-1 molecular sieve with a high silicon-to-aluminum molar ratio.
[0021] In some embodiments, the template includes hexamethylammonium bromide. In some embodiments, the template also includes one or more of benzyldimethylamine, tetramethylammonium bromide, tetraethylammonium bromide and tetrapropylammonium bromide. In some specific embodiments, the template includes hexamethylammonium bromide and tetramethylammonium bromide. In some specific embodiments, the template includes hexamethylammonium bromide and tetraethylammonium bromide. In some specific embodiments, the template includes hexamethylammonium bromide and tetrapropylammonium bromide.
[0022] In some embodiments, in the mixed solution, the silicon source is calculated as SiO2, the inorganic alkali source is calculated as the corresponding alkali metal oxide M2O, and the molar ratio of SiO2 to M2O is 1:0.2-0.5, for example, it can be 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5 or any value therebetween, preferably 1:(0.25-0.4).
[0023] In some embodiments, in the mixed solution, the silicon source is calculated as SiO2, and the molar ratio of SiO2 to the template is 1:(0.1-0.6), for example, it can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6 or any value therebetween, preferably 1:(0.3-0.6).
[0024] In some embodiments, in the mixed solution, the silicon source is calculated as SiO2, and the molar ratio of SiO2 to water is 1:10-80, for example, it can be 1:10, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:60, 1:70, 1:80 or any value therebetween, preferably 1:(25-40).
[0025] In some embodiments, in the mixed solution, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the inorganic alkali source is calculated as the corresponding alkali metal oxide M2O, and the molar ratio of SiO2:Al2O3:M2O=1:(0.001-0.003):(0.2-0.5).
[0026] In some embodiments, in the mixed solution, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the molar ratio of SiO2:Al2O3:template=1:(0.001-0.003):(0.1-0.6).
[0027] In some embodiments, in the mixed solution, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the inorganic alkali source is calculated as the corresponding alkali metal oxide M2O, and the molar ratio of SiO2:Al2O3:M2O:template is 1:(0.001-0.003):(0.2-0.5):(0.1-0.6).
[0028] In some embodiments, in the mixed solution, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the inorganic alkali source is calculated as the corresponding alkali metal oxide M2O, and the molar ratio of SiO2:Al2O3:M2O:template:H2O=1:(0.001-0.003):(0.2-0.5):(0.1-0.6):(10-80).
[0029] In some preferred embodiments, in the mixed solution, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the inorganic alkali source is calculated as the corresponding alkali metal oxide M2O, and the molar ratio of SiO2:Al2O3:M2O:template:H2O=1:(0.0012-0.0025):(0.25-0.4):(0.3-0.6):(25-40).
[0030] In the present invention, there are no special requirements for the crystallization conditions such as temperature, time, and pressure. In some embodiments, the crystallization temperature is 120-200°C. In some embodiments, the crystallization temperature is 150-190°C. In some embodiments, the crystallization temperature is 170-190°C. In some embodiments, the crystallization time is 48-72h.
[0031] In some embodiments, the crystallization is performed in an autoclave.
[0032] In some embodiments, the crystallization is carried out in a high gravity reactor. In some specific embodiments, the rotation speed of the high gravity reactor is 120-1500 rpm. In some specific embodiments, the rotation speed of the high gravity reactor is 800-1200 rpm. In some specific embodiments, the feed rate of the high gravity reactor is 50-200 mL·min -1 In some embodiments, the feed rate of the high gravity reactor is 80-150 mL·min -1 .
[0033] In some embodiments, the method further comprises: a step of aging the mixed solution before crystallization. In the present invention, there are no special requirements for the aging conditions such as temperature and time. In some embodiments, the aging is dynamic aging. In some specific embodiments, the aging temperature is 15-40°C and the aging time is 8-16h. In some specific embodiments, the aging temperature is 15-40°C and the aging time is 12-16h.
[0034] In some embodiments, the method further comprises: a step of post-treating the crystallization liquid after crystallization. The post-treatment refers to a process of treating the crystallization liquid obtained after crystallization to obtain a molecular sieve. In some embodiments, the post-treatment comprises solid-liquid separation, washing and heat treatment. In some embodiments, the heat treatment comprises drying and calcining.
[0035] The present invention has no special requirements for the steps and conditions of the solid-liquid separation, washing and heat treatment, and can be carried out in any manner conventionally known in the art. Specifically, as the solid-liquid separation, filtration can be performed, such as simply filtering the obtained crystallized liquid. As the washing, for example, washing with deionized water can be cited. As the drying temperature, for example, 40-250°C, preferably 60-150°C, can be cited as the drying time, for example, 8-30 hours, preferably 10-20 hours can be cited. Drying can be carried out at normal pressure or under reduced pressure. In some specific embodiments, the drying temperature is 40-150°C, and the drying time is 8-20h. The roasting can be carried out in any manner conventionally known in the art, such as a roasting temperature of generally 300-800°C, preferably 400-650°C, and a roasting time of generally 1-10 hours, preferably 3-6 hours. In addition, the roasting is generally carried out in an oxygen-containing atmosphere, such as air or oxygen atmosphere. In some specific embodiments, the calcination temperature is 500-600° C., and the calcination time is 3-6 hours.
[0036] In a third aspect, the present invention provides the use of the flaky EU-1 molecular sieve described in the first aspect in catalysis, adsorption and ion exchange.
[0037] The flaky EU-1 molecular sieve of the present invention can be used as an adsorbent, for example, to separate at least one component from a mixture of multiple components in a gas phase or a liquid phase. Accordingly, the at least one component can be partially or substantially completely separated from the mixture of various components, for example, by contacting the mixture with the flaky EU-1 molecular sieve to selectively adsorb the component.
[0038] In addition, the flaky EU-1 molecular sieve of the present invention can also be used as a catalyst, for example, to catalyze reactions such as aromatic conversion, methanol to propylene (MTP) and naphtha cracking.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The flaky EU-1 molecular sieve of the present invention is different from the existing EU-1 molecular sieve in morphology, and has a high silicon-aluminum ratio, a large specific surface area, and high catalytic performance and stability.
[0041] 2. The preparation method of the present invention does not require the addition of seed crystals or the use of high-cost organic bases. By selecting a specific material ratio, a pure-phase, high-silicon-to-aluminum-ratio thin-sheet EU-1 molecular sieve can be obtained in one step.
[0042] 3. The preparation method of the present invention has simple process, cheap and easily available raw materials, high reaction efficiency, high product crystallinity, high method stability, low cost, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the XRD spectrum of the EU-1 molecular sieve prepared in Example 1 of the present invention.
[0044] Figure 2 This is a SEM photograph of the EU-1 molecular sieve prepared in Example 1 of the present invention.
[0045] Figure 3 This is the XRD spectrum of the EU-1 and ZSM-48 mixed molecular sieve prepared in Comparative Example 1.
[0046] Figure 4 This is the SEM photograph of the rugby-shaped EU-1 molecular sieve prepared in Comparative Example 2. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.
[0048] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0049] In this paper, the structure of the molecular sieve is determined by an X-ray diffraction spectrum (XRD), which is measured by an X-ray powder diffractometer using a Cu-Kα ray source with a Kα1 wavelength of λ = 1.5405980 angstroms. Nickel filter.
[0050] In the present invention, an X'PertPRO X-ray powder diffraction (XRD) instrument of PANalytical Company of the Netherlands is used, with an operating voltage of 40 kV, a current of 40 mA, and a scanning range of 5 to 40°.
[0051] In the present invention, the scanning electron microscope (SEM) image was obtained by a Japanese HITACHIS4800 field emission scanning electron microscope, and the test conditions were as follows: voltage 3 kV, current 50 mA.
[0052] Unless otherwise specified, the instruments, equipment and reagents used in the following examples and comparative examples of the present invention can be obtained through commercial channels. The ultra-gravity crystallization device used was produced by Nanjing Hengge Water Treatment Technology Co., Ltd., and its operating parameters were: feed rate 50-200 mL·min -1 , rotation speed 120-1500rpm, crystallization temperature 150-200℃, crystallization time 48-72h. In the embodiment, the feed rate is 100mL·min -1 .
[0053] Example 1
[0054] Weigh 2.4g of sodium hydroxide and add it to 65g of deionized water. After vigorous stirring, add 0.023g of sodium aluminate. After stirring until completely dissolved, weigh 10g of hexamethylammonium bromide and add it to the mixed solution. After stirring for one hour, add 5g of tetraethylammonium bromide until it is completely dissolved. Stir vigorously for one hour, and finally add 15g of silica sol (40wt%) dropwise. The gel mixture is placed at room temperature for dynamic aging for 12h and then transferred into a stainless steel autoclave with a polytetrafluoroethylene liner. The temperature is set at 170℃ for crystallization for 72h. After cooling, washing and drying, the original powder of EU-1 molecular sieve can be obtained. The original powder of EU-1 molecular sieve is placed in a muffle furnace and calcined at 550℃ for 5h to remove the template agent to obtain EU-1 molecular sieve. X-ray diffraction (XRD) inspection shows that it is a pure phase EU-1 molecular sieve, and the silicon-aluminum molar ratio of the product is SiO2 / Al2O3=680.
[0055] Figure 1 The XRD spectrum of the prepared EU-1 molecular sieve is Figure 1 It can be seen that the synthesized product is a pure phase EU-1 molecular sieve.
[0056] Figure 2 This is the SEM photo of the prepared EU-1 molecular sieve. Figure 2 It can be seen that the morphology of the synthesized EU-1 molecular sieve is different from the rugby-shaped morphology of the conventional EU-1 molecular sieve. It is in the form of thin flakes with a layer thickness of 35 nm.
[0057] Example 2
[0058] Weigh 3.2g potassium hydroxide and add it to 60g deionized water. Stir until completely dissolved, weigh 0.04g sodium aluminate and add it to the mixed solution. After stirring for one hour, add 13g hexamethylammonium bromide until it is completely dissolved, and finally add 15g silica sol (40wt%) dropwise. The gel mixture is placed at room temperature for dynamic aging for 15h and then transferred to an ultra-gravity crystallization device. The speed is set to 1000rpm and the temperature is 180℃ for crystallization for 60h. After cooling, washing and drying, the original powder of EU-1 molecular sieve can be obtained. The original powder of EU-1 molecular sieve is placed in a muffle furnace and calcined at 560℃ for 3h to remove the template agent to obtain a flaky EU-1 molecular sieve. X-ray diffraction (XRD) inspection shows that it is a pure phase EU-1 molecular sieve, and the silicon-aluminum molar ratio of the product is SiO2 / Al2O3=370.
[0059] Example 3
[0060] Weigh 2.4g of sodium hydroxide and add it to 55g of deionized water. After vigorous stirring, add 0.025g of sodium aluminate. After stirring until completely dissolved, weigh 8g of hexamethylammonium bromide and add it to the mixed solution. After stirring for one hour, add 1.5g of tetramethylammonium bromide until it is completely dissolved. Finally, add 15g of silica sol (40wt.%) dropwise. The gel mixture is placed at room temperature for dynamic aging for 16h and then transferred to an ultragravity crystallization device. The speed is set to 1000rpm and the temperature is 190℃ for crystallization for 48h. After cooling, washing and drying, the original powder of EU-1 molecular sieve can be obtained. The original powder of EU-1 molecular sieve is placed in a muffle furnace and calcined at 580℃ for 3h to remove the template agent to obtain a sheet of EU-1 molecular sieve. X-ray diffraction (XRD) inspection shows that it is a pure phase EU-1 molecular sieve, and the silicon-aluminum molar ratio of the product is SiO2 / Al2O3=600.
[0061] Example 4
[0062] Weigh 3.0g potassium hydroxide and add it to 60g deionized water. Stir until completely dissolved, weigh 0.02g sodium aluminate and add it to the mixed solution. After stirring for one hour, add 13g hexamethylammonium bromide until it is completely dissolved, and finally add 15g silica sol (40wt%) dropwise. The gel mixture is placed at room temperature for dynamic aging for 15h and then loaded into a stainless steel autoclave with a polytetrafluoroethylene liner. It is statically crystallized at 180℃ for 60h. After cooling, washing and drying, the molecular sieve raw powder can be obtained. The molecular sieve raw powder is placed in a muffle furnace and roasted at 560℃ for 3h to remove the template. X-ray diffraction (XRD) inspection shows that it is EU-1 molecular sieve, and SEM photos show that the product has a flaky structure.
[0063] Comparative Example 1
[0064] The method of Example 1 was followed, except that the template agent was different: no hexamethylammonium bromide was added, and only 5 g of the template agent tetraethylammonium bromide was added. The other conditions were the same, and X-ray diffraction (XRD) analysis showed that the product was a mixed molecular sieve of EU-1 and ZSM-48.
[0065] Figure 3 The XRD spectrum of the EU-1 and ZSM-48 mixed molecular sieve prepared in Comparative Example 1 is shown in FIG. Figure 3 It can be seen that in addition to the characteristic peaks of EU-1 molecular sieve, characteristic peaks of ZSM-48 molecular sieve also appeared, and pure phase EU-1 molecular sieve could not be synthesized.
[0066] Comparative Example 2
[0067] Weigh 1g of sodium hydroxide and add it to 60g of deionized water. Stir until completely dissolved, then weigh 0.1g of sodium aluminate and add it to the mixed solution. After stirring for one hour, add 5g of hexamethylammonium bromide and stir vigorously for one hour. Finally, add 15g of silica sol (40wt%) dropwise. The gel mixture is placed at room temperature for dynamic aging for 16 hours and then loaded into a stainless steel autoclave with a polytetrafluoroethylene lining. It is statically crystallized at 190℃ for 48 hours. After cooling, washing and drying, the original molecular sieve powder can be obtained. The original molecular sieve powder is placed in a muffle furnace and roasted at 580℃ for 3 hours to remove the template. X-ray diffraction (XRD) inspection shows that it is EU-1 molecular sieve.
[0068] Figure 4 This is a SEM photo of the EU-1 molecular sieve prepared in Comparative Example 2; Figure 4 It can be seen that the synthesized EU-1 molecular sieve has a rugby-shaped morphology.
[0069] Comparative Example 3
[0070] The only difference from Example 1 is that the amount of template agent tetraethylammonium bromide used is 10 g. The final synthesized product is irregular granular without flaky structure.
[0071] Comparative Example 4
[0072] The only difference from Example 1 is that the amount of sodium hydroxide used is 0.8 g. X-ray diffraction (XRD) test shows that the final synthesized product is a mixed molecular sieve of EU-1 and ZSM-48.
[0073] Comparative Example 5
[0074] The only difference from Example 1 is that the amount of sodium hydroxide used is 4.8 g. The final synthesized product is irregular granular without a flaky structure. It can be seen from the above Examples 1-4 that the method of the present invention can obtain EU-1 pure phase molecular sieves with different silicon-aluminum molar ratios by controlling the dosage ratio of the inorganic alkali source, silicon oxide, aluminum oxide, template agent, etc.
[0075] Analysis of experimental results: From the comparison of the results of Comparative Example 1 and Example 1, it can be seen that the present invention uses only tetraethylammonium bromide as a template agent without adding hexamethylammonium bromide, and cannot synthesize a pure phase EU-1 molecular sieve. From Comparative Examples 2-5 compared with Examples 1-4, the usage ratio of inorganic alkali source, silicon oxide, aluminum oxide, template agent, etc. needs to be controlled within a suitable range, otherwise a sheet-like structure of EU-1 pure phase molecular sieve cannot be obtained.
[0076] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A sheet-like EU-1 molecular sieve, the sheet thickness of which is 20-50 nm.
2. The molecular sieve according to claim 1, characterized in that The specific surface area of the molecular sieve is greater than 200m 2 ·g -1 ; and / or, the silicon-aluminum molar ratio SiO2 / Al2O3 of the molecular sieve is 350-700.
3. A method for preparing the sheet-like EU-1 molecular sieve according to claim 1 or 2, comprising the following steps: A mixed solution containing an inorganic alkali source, an aluminum source, a template, a silicon source and water is crystallized to obtain a sheet-like EU-1 molecular sieve, wherein: In the mixed solution, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the molar ratio of SiO2 to Al2O3 is 1:(0.001-0.003), preferably 1:(0.0012-0.0025).
4. The method according to claim 3, characterized in that The inorganic alkali source is at least one of alkali metal oxides, alkali metal hydroxides, and alkali metal carbonates, preferably at least one of lithium hydroxide, sodium hydroxide, and potassium hydroxide; and / or, The silicon source is selected from one or more of silica sol, water glass and silicate; and / or, The aluminum source is selected from one or more of sodium aluminate, aluminum nitrate nonahydrate, pseudo-boehmite and aluminum isopropoxide; and / or, The template agent includes hexamethylammonium bromide. Optionally, the template agent also includes one or more of benzyldimethylamine, tetramethylammonium bromide, tetraethylammonium bromide and tetrapropylammonium bromide.
5. The method according to claim 3 or 4, characterized in that: In the mixed solution, the inorganic alkali source is calculated as the corresponding alkali metal oxide M2O, and the molar ratio of SiO2 to M2O is 1:(0.2-0.5), preferably 1:(0.25-0.4); and / or, the molar ratio of SiO2 to the template is 1:(0.1-0.6), preferably 1:(0.3-0.6); and / or, the molar ratio of SiO2 to water is 1:(10-80), preferably 1:(25-40).
6. The method according to any one of claims 3 to 5, characterized in that: In the mixed solution, the inorganic alkali source is calculated as the corresponding alkali metal oxide M2O, and the molar ratio of SiO2:Al2O3:M2O:template:H2O=1:(0.001-0.003):(0.2-0.5):(0.1-0.6):(10-80); Preferably, in the mixed solution, the molar ratio of SiO2:Al2O3:M2O:template:H2O=1:(0.0012-0.0025):(0.25-0.4):(0.3-0.6):(25-40).
7. The method according to any one of claims 3 to 6, characterized in that: The crystallization temperature is 120-200° C., preferably 150-190° C.; the crystallization time is 48-72 hours.
8. The method according to any one of claims 3 to 7, characterized in that: The crystallization is carried out in a high gravity reactor; Preferably, the rotation speed of the supergravity reactor is 120-1500 rpm, preferably 800-1200 rpm; Preferably, the feed rate of the supergravity reactor is 50-200 mL min -1 , preferably 80-150 mL·min -1 .
9. The method according to any one of claims 3 to 8, characterized in that: The method further comprises: a step of aging the mixed solution before crystallization, and / or a step of post-treating the crystallized solution after crystallization, wherein the post-treatment comprises solid-liquid separation, washing, drying and calcining; Preferably, the aging temperature is 15-40°C and the aging time is 8-16h; Preferably, the drying temperature is 40-150°C; the drying time is 8-20h; Preferably, the calcination temperature is 500-600° C. and the calcination time is 3-6 hours.
10. Use of the flaky EU-1 molecular sieve according to claim 1 or 2 in catalysis, adsorption and ion exchange.
Citation Information
Patent Citations
Preparation method of EU-1 molecular sieve catalyst used in high-selectivity propylene preparation by using methanol
CN103301877A
Method for preparing EUO type structural zeolite and its use as catalyst
CN1259399A
Mixed crystal material containing EUO zeolite and preparation method thereof
CN102416345A
Hierarchical-pore EUO structure molecular sieve and synthesis method thereof
CN108946756A
Preparation method of EUO molecular sieve
CN115072736A
Cited By
High-silicon hierarchical pore EU-1 molecular sieve and synthesis method thereof
CN121405105A